Are the Derived Indexes of Peripheral Whole Blood Cell Counts (NLR, PLR, LMR/MLR) Clinically Significant Prognostic Biomarkers in Multiple Myeloma? A Systematic Review And Meta-Analysis - Zhang, Xinwen; Duan, Jialin; Wen, Zhenyu; Xiong, Hao; Chen, Xiaomin; Liu, Yang; Liao, Kunyu; Huang, Chunlan (Frontiers in Oncology, 2021)
Background Multiple myeloma (MM) is an incurable malignant plasma cell tumor. Whole blood cell count (WBCC) derived indexes are widely used as a predictive biomarker for various types of solid and hematological malignant tumors. Our study is to evaluate its effectiveness in MM by meta-analysis. Methods Relevant literatures were retrieved from PubMed, Embase and Web of Science databases according to PRISMA guideline. All relevant parameters were extracted and combined for statistical analysis. Results Nineteen studies incorporating 3818 MM patients were eventually included in this meta-analysis. 13 studies evaluated that elevated NLR was significantly associated with poor survival outcomes (OS: HR=2.04, P<0.001; PFS: HR=1.96, P=0.003). Elevated NLR was revealed to correlate with ISS stage (ISS III VS I-II, OR=2.23, P=0.003). A total of 7 studies have shown that elevated LMR predicts a better prognosis in MM patients (OS: HR=0.57, P<0.001; PFS: HR=0.49, P<0.05), and two other studies demonstrated that increased MLR was related to poor OS/PFS (OS: HR=1.58, P<0.05; PFS: HR=1.60, P<0.05). However, in the other 6 studies including 1560 patients, the prognostic value of PLR had not been confirmed (OS: HR=0.89, P>0.05; PFS: HR=0.87, P>0.05). Conclusions The indexes NLR and LMR/MLR derived from WBCC were validated to be useful biomarkers to predict the prognosis in MM patients, but the evidence of PLR was insufficient.